SAID: A Social Media AI-generated Interface Dataset Using Prompt Engineering Methods Focused On Accessibility - Guriță, Alexandra-Elena (Proceedings of the International AAAI Conference on Web and Social Media, 2025)
We present SAID (Social Media AI-generated Interface Dataset), a systematically curated collection of 240 social media profile interfaces generated through controlled prompt engineering focused on accessibility. As AI tools reshape interface design practices, understanding how these systems interpret and implement accessibility requirements in social media interfaces becomes more and more important. Through six distinct prompt categories examining both generic and specific accessibility requirements, our dataset captures how AI systems interpret and implement accessibility features across visual and motor impairment dimensions. The dataset combines complete interface designs in multiple formats (PNG and SVG), detailed prompt engineering methodology, and comprehensive documentation of interface components such as social identity presentation, content engagement, navigation, and interactive elements. SAID enables novel research directions from understanding AI’s role in shaping accessible social media experiences to examining how automated design tools can support more inclusive social interactions.